Spatial characteristics of physical environments for human settlements in Jinsha River watershed (Yunnan section), China - Jisheng Xia; Pinliang Dong (Geomatics, Natural Hazards & Risk, 2019)
In recent years, natural disasters such as earthquakes, landslides, mudslides, collapses, drought, and extreme temperature occur frequently in Yunnan Jinsha River watershed, causing deterioration of physical environments for human settlements in some areas of the watershed. Although several studies have addressed individual environmental elements in the study area, efforts for integrated analysis of environmental factors and human settlements are still lacking. Therefore, it is important to identify the spatial distribution of physical environments for human settlements to support population distribution planning. This study includes 10 factors (topography, landform, vegetation, elevation, fault, rock, soil, earthquake intensity, temperature, and precipitation) as indicators for the assessment of human settlement suitability based on the analytic hierarchy process and grey correlation methods. Geographic information system functions were used to help understand the spatial distribution of human settlements and the causal factors. This study reveals different spatial units of the watershed suitable for human habitation from the viewpoint of physical environment and provides recommendations for urban planning and siting, land use planning, and disaster mitigation in the watershed.